(3JMQjQ GdJLGQI GdOhdjI habG dGJaGbjI GdLGJ aj eLGd GdNOeGJ (B/s - (3YeGQI, QGfjG eMehO YHO GdYRjRs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2007)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3GdLhdGJ h GdeaGhVGJ GdNGUI HGdEJaGbjI GdYGeI ddJYQjaGJ h GdJLGQI,GdbhGYO GdYGeI GdJj JMce efXeI GdJLGQI GdYGdejI,GdEJaGbjI GdYGeI ddJLGQI aj GdNOeGJ,GdEJaGbjI h GdJfXje GdbGfhfj GdOhdj dJLGQI GdNOeGJ,OQGSI JaUjdjI Yf GdNOeGJ GdeGdjI h GdeUQajI,GdBKGQ GdeJQJHI Yf JMQjQ GdNOeGJ GdeGdjI h GdeUQajI aj eUQ,eGgjI ejRGf GdeOahYGJ,GdfXQjGJ GdEbJUGOjI h JhGRf ejRGf GdeOahYGJ,echfGJ ejRGf GdeOahYGJ GdeUQj,BKGQ JWHjb GdEJaGbjI GdYGeI ddJLGQI aj GdNOeGJ Ydi ejRGf GdNOeGJ GdeUQj(B.s
Keywords: (3GdJLGQI GdOhdjIs; (3GdLGJs; (3ejRGf GdeOahYGJs